Functionalization of Osteoplastic Material with Human Placental Growth Factor and Assessment of Biocompatibility of the Resulting Material In Vitro - Diana Ya Aleynik; Andrey E. Bokov; Irina N. Charykova; Yulia P. Rubtsova; Daria D. Linkova; Ekaterina A. Farafontova; Marfa N. Egorikhina (MDPI AG, 2024)
This article provides the results of a study of the interaction of placental growth factor with adipose-derived stem cells (ASCs) of various origins, as well as the possibility of generating osteoplastic material based on xenogeneic matrix functionalization with human placental growth factor (PLGF). It is demonstrated that the greatest release of this factor from the functionalized material into the medium occurs during the first 3 h of contact with the model medium, but then the levels of the factor being released fall sharply, although release did continue throughout the 7 days of observation. The modified material was not cytotoxic, and its surface provided good cell adhesion. During 3 days of cultivation, the ASCs proliferated and migrated more actively on the surfaces of the modified material than on the surfaces of the control material. This study can serve as the basis for the development of original methods to functionalize such osteoplastic material by increasing PLGF immobilization by creating stronger bonds in order to regulate both factor dosage and the dynamics of the factor release into the environment. Further studies in experimental animals should facilitate assessment of the effectiveness of the functionalized materials. Such studies will be useful in the development of osteoplastic materials with new properties resulting from the inclusion of growth factors and in research on their biological activity.